THE USE OF REAP (READING, ENCODE, ANNOTATE AND PONDER) TECHNIQUE IN TEA CHING READING ANALYTICALEXPOSITION FOR THE ELEVENTH GRADE STUDENTS IN SMAN 17 MEDAN - Sarah Azryani Hasibuan; Masitowarni Siregar; Rafika Dewi Nasution (Universitas Negeri Medan, 2020)
This study aimed at describing the use of REAP technique and investigating the reasons of using REAP technique in teaching reading analytical exposition text grade eleven at SMAN 17 Medan in the academic year of 2019/2020. This study was descriptive qualitative conducted that taken one English teacher of SMAN 17 Medan. The data were collected by using an interview and observing the whole process of teaching reading analytical exposition text. The findings of this study showed that the teacher implemented four steps of REAP technique in teaching reading analytical exposition text. The teacher did every step with a good performance. The reasons of using REAP technique in teaching reading analytical exposition text were a fresh way to think to understand a text easily, encouraged students to think critically on the issues discussed, developed reading and writing skill, and also vocabulary. It also found a reason that students were easily invited to explore their ideas on the issues discussed. The findings of this study revealed that REAP technique contributed to the study of foreign language teaching especially teaching reading skill.Keywords: REAP technique, reading, analytical exposition text.